Polyorchidism. Issue 742 (August 1987) - Haddock, G.; Burns, H. J.
Abstract : Polyorchidism is an unusual abnormality of the genital tract in which supernumerary testes are present, usually within the scrotum. We report a recently encountered case, discuss the aetiology of the condition and suggest a course of management when encountered at operation.